INTEGRASI NILAI-NILAI ISLAM DALAM HUKUM PUBLIK ZAKAT OLEH PEMERINTAH PROVINSI BENGKULU) - Imam Mahdi (Universitas Islam Negeri Fatmawati Sukarno, 2015)
Abstract: Zakat is the economic potential of the Muslims, has some of the most important aspects is the social aspect so that there is no interaction between the aghniya and dhu’afa. While countries including the region must alleviate the poor and needy, as mandated in the Constitution NRI Year 1945. As a Muslim-majority country that zakat should be a priority in its management, it is almost certain that the Muslims who have wealth to pay zakat.Persolannya is how far the state will adopt the values of Islamic economics. This paper is the result of empirically, answering the question raised, it was the Government and Local Government has menngintegrasikannya in the regulation. Only in the implementation of several policies not maximized, because the implementation is still applied to civil servants, not to the public at large, whereas the economic potential of the people, scattered in among economic actors. Zakat institutions established by the government, has not been acted upon maximumduty, particularly in exploring the potential of zakat outside the bureaucratic environment. For example zakat in the city of Bengkulu people more engaged in services and economic activity, far behind from the community Rejang Lebong majority of farmers in the collection of zakat through BAZNAS.